An investigation into the impact of digitalization in the SME’s development in Namibia: a systematic literature review - Angula, Nikodemus (BOHR International Journal of Advances in Management Research, 2024)
The study sought to determine how digitalization has affected the growth of SME’s in Namibia. Using secondary data, the study examined how digitization has affected the growth of SMEs in Namibia and around the world. To ascertain whether technologies are used in businesses in Namibia and elsewhere, a survey of pertinent literature on digitalization in the development of SMEs was done. Numerous SMEs in Namibia face challenges such as increased rivalry and an inability to adapt to rapidly shifting market demand, technological development, and capacity restrictions brought on by knowledge, innovation, and creativity. According to the present survey, SMEs in Namibia should begin utilizing digitalization because it offers insights that help them better understand their clients and gauge the effectiveness of marketing initiatives. This is especially helpful for small businesses with constrained marketing budgets